Mapping a Potential Location of Temporary Waste Storage Sites (TPS) in Sorong and East Sorong Districts using Geographic Information Systems (GIS) - Pramono, Azzahra Cahya; Pratiwi, Yuli; Muchlis (Engineering And Technology Journal, 2024)
Garbage is the result of waste from the activities of living things that are often encountered and cause many problems. One way to overcome the waste problem is to provide TPS. One area in Indonesia that does not yet have TPS facilities is in East Sorong and Sorong Districts, West Papua. This study aims to 1) determine the location of TPS in East Sorong District and Sorong District using the Geographic Information System (GIS), 2) knowthe recommended TPS type based on the mapping of TPS locations using GIS, 3) know the amount of waste generation in Sorong District East and Sorong District. The research phase begins with determining the sample TPS locations by looking at the parameters of the distance to built-up land, the main road and the river. Mapping the suitability of TPS locations using the GIS application. Determination of waste samples and waste collection to calculate the amount of waste generation. The recommended locations for TPS construction in East Sorong District and Sorong District based on the results of analysis using GIS and field surveys are: a) East Sorong District, which consists of the Klamana Village, the Klawuyuk Village, and the Klawalu Village. b) Sorong District, which consists of North Remu Village and Klademak Village. Waste generation in East Sorong District is 0.00816kg/person/day and Sorong District is 0.0122 kg/person/day.